2019
DOI: 10.1186/s12879-019-4283-x
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcome of a community-based hepatitis B awareness campaign: eight-year follow-up on linkage to care (LTC) in HBV infected individuals

Abstract: Background Chronic hepatitis B (CHB) is a major cause of liver-related morbidity and mortality. High HBV prevalence in immigrants and ethnic minorities and numerous barriers to healthcare access are associated with serious health disparities in the United States. Reportedly, self-awareness of HBV infection is low, suggesting a greater need for effective screening and education. Further, low levels of linkage to care (LTC) (completion of a first doctor’s visit after the diagnosis of chronic HBV inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
(35 reference statements)
1
8
0
Order By: Relevance
“…The researchers concluded that despite having HBV guidelines for diagnosing and treating HBV in Europe, policies for diagnostics and treatment varied significantly across Europe. Similar findings were found in the US when comparing those on government‐sponsored insurance (Medicaid) vs those who received their healthcare through the private market 82 …”
Section: Gaps In Screening Diagnosis and Connection To Care For Infesupporting
confidence: 66%
“…The researchers concluded that despite having HBV guidelines for diagnosing and treating HBV in Europe, policies for diagnostics and treatment varied significantly across Europe. Similar findings were found in the US when comparing those on government‐sponsored insurance (Medicaid) vs those who received their healthcare through the private market 82 …”
Section: Gaps In Screening Diagnosis and Connection To Care For Infesupporting
confidence: 66%
“…28,32 Given that the majority burden of CHB in the United States is seen among Asian and African immigrants, the higher rates of treatment in these groups may be a result of greater awareness of the disease burden among these populations, which are enriched in non-speaking immigrants and indigent care populations. 33,34 The observations of alarmingly low rates of CHB treatment among safety-net populations needs to prompt greater focus on interventions to improve these disparities. While drivers of these disparities are multifactorial, recent studies have demonstrated the importance of provider and patient knowledge in improving HBV monitoring and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…TABLE 4 Odds of maintaining UTD* status for patients with chronic HBV infection at 6 months for those who were UTD at baseline and odds of achieving UTD status at 6 months for those who were not UTD at baseline for three groups, 1) CIH pilot, 2) Gastroenterology, and 3) HP PC; N 5 4,872 Although we are unaware of other EHR-integrated CHB registries in the United States focused on improving long-term management of CHB infected patients, community-based hepatitis B education campaigns have shown the importance of long-term linkage to care. 22 Standardized education was not a specific intervention in our study; however, patients' HBV infection was discussed during outreach efforts and clinic visits. These discussions likely provided patient education about both hepatitis B in general and the need for routine monitoring.…”
Section: Discussionmentioning
confidence: 94%
“…Although we are unaware of other EHR-integrated CHB registries in the United States focused on improving long-term management of CHB infected patients, community-based hepatitis B education campaigns have shown the importance of long-term linkage to care. 22 Standardized education was not a specific intervention in our study; however, patients’ HBV infection was discussed during outreach efforts and clinic visits. These discussions likely provided patient education about both hepatitis B in general and the need for routine monitoring.…”
Section: Discussionmentioning
confidence: 96%